Effect of post-treatment on the microstructure and high-temperature oxidation behaviour of additively manufactured inconel 718 alloy. (September 2019) - Kang, Yeon-Ji; Yang, Sangsun; Kim, Young-Kyun; AlMangour, Bandar; Lee, Kee-Ahn
Highlights: Post-treatment processing of additively manufactured Inconel 718 alloy were investigated Hot isostatic pressing enhanced corrosion protection compared to solution ageing. Different grain boundary microstructures were developed during post-treatments Graphical abstract: Abstract: The effect of solution ageing and hot isostatic pressing treatments on the high-temperature (900, 1000 °C) oxidation of selective laser melted Inconel 718 alloy was studied. Oxidation results showed improved oxidation resistance after HIP treatment, attributed to higher density of the HIP sample and microstructural differences at the grain boundaries. Cations diffused along the grain boundary in SA alloy, while Ti-rich carbides retarded grain boundary diffusion in HIPed alloy. In SA alloy, the γ" and δ phases were observed within the grain, and at the molten pool boundary, respectively. In HIPed alloy, discontinuous MC were observed, along with fine γ' phases.